Application of nitric boron nitride fibers
By replacing the nitrocellulose membrane with boron nitride fibers, the problem of insufficient detection sensitivity, mechanical strength and stability in cancer prognosis test strips was solved, and higher detection performance and better technical performance were achieved.
Patent Information
- Application Number
- CN202411622726.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-11
AI Technical Summary
The fragility of the nitrocellulose membrane in the existing cancer prognosis test strips, low protein binding capacity, high background signal, sensitivity to humidity and temperature, and limited chemical tolerance, resulting in insufficient detection sensitivity, mechanical strength and stability.
Boron nitride nitride fibers are used as a substitute for nitrocellulose membranes, and their detection performance in cancer prognosis test strips is improved through specific preparation processes and loading methods.
It improves the detection sensitivity, mechanical strength and stability of cancer prognosis test strips, and fills the technical gap in boron nitride-based nitrocellulose membrane replacement products.
Smart Images

Figure CN119411423A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical detection, and specifically relates to a new use of oxidized boron nitride fiber, specifically, an application as a substitute for nitrocellulose membrane in cancer prognosis test strips. Background Art
[0002] With the increasing demand for cancer postoperative follow-up and monitoring of recurrence risk, the development of cancer prognosis test strips has been rapid. It is well known that nitrocellulose membrane, as an important component of cancer prognosis test strips, has a great influence on the sensitivity and accuracy of its detection and is the guarantee for its efficient and reliable detection. However, nitrocellulose membrane has the following main disadvantages: (1) It is relatively brittle and easy to tear during operation, and often requires extra caution in handling, otherwise it will lead to detection failure; (2) The low protein binding capacity and high background signal affect its application in high-sensitivity detection with high requirements; (3) It is sensitive to changes in humidity and temperature and needs to be stored in a dry and cool environment to ensure its performance; (4) It has limited chemical tolerance and requires organic solvents and pH conditions, otherwise it may cause degradation or denaturation, thereby affecting the detection results. Therefore, it is very necessary to develop a nitrocellulose membrane substitute for cancer prognosis test strips to improve the detection sensitivity, mechanical strength and stability of cancer prognosis test strips.
[0003] In view of this, the present invention discloses a substitute for nitrocellulose membrane in a cancer prognosis test strip, namely, oxidized boron nitride fiber, so as to improve the detection sensitivity, mechanical strength and stability of the cancer prognosis test strip. Summary of the invention
[0004] In view of the shortcomings of nitrocellulose membranes in cancer prognosis test strips and the lack of abundant substitutes therefor, the present invention provides a substitute for nitrocellulose membranes in cancer prognosis test strips, namely, oxidized boron nitride fiber, and provides a preparation process thereof, which fills the technical gap of the lack of boron nitride nitrocellulose membrane substitutes in the prior art, while improving the detection sensitivity, mechanical strength and stability of cancer prognosis test strips.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is: The invention provides an application of oxidized boron nitride fiber as a substitute for nitrocellulose membrane in a cancer prognosis test strip in cancer prognosis monitoring.
[0006] Preferably, the inventors have verified that the cancer for which oxidized boron nitride fiber is effective in replacing nitrocellulose membrane in cancer prognosis test strips is ovarian cancer, proving that oxidized boron nitride fiber is a potential substitute for nitrocellulose membrane in other cancer prognosis test strips.
[0007] Preferably, the diameter of the oxyboron nitride fibers is 0.1-1.2 microns.
[0008] Preferably, the mass percentage content of oxygen in the oxidized boron nitride fiber is 38.7%-40.3%.
[0009] Preferably, the diffraction angle of the XRD characteristic peak of the oxidized boron nitride fiber is consistent with the characteristic peak of the oxidized boron nitride standard (JCPDS-29-1216).
[0010] Preferably, the oxidized boron nitride fibers have an overall electronegativity, an isoelectric point of 3-5, a zeta potential between -10 mV and -30 mV, and a surface charge density of -0.1 to -0.3 μC / cm².
[0011] Preferably, the method for preparing the oxidized boron nitride fiber comprises the following steps: The first step is to dissolve 10-20 g of TEA-B and triethoxyborane in a molar ratio of 1:1.5-2 in 100 mL of anhydrous ethanol, and add 0.1 ml of hydrochloric acid; the second step is to stir the solution formed in the first step at room temperature for about 2 hours until a uniform sol is formed; the third step is to spin the sol prepared in the second step through a wet spinning process, The method comprises the following steps: extruding the raw material through a spinneret with a diameter of mm, the ambient temperature being 20-25 degrees Celsius and the humidity being 40-50%; fourthly, drying the initial fiber obtained in the third step at 60-80 degrees Celsius for 12 hours; fifthly, preheating and decomposing the gel fiber obtained in the fourth step at 500 degrees Celsius in nitrogen for 1 hour, then heating the gel fiber to 1200 degrees Celsius and heat treating the fiber in a nitrogen atmosphere with an oxygen content of 0.1-0.5% for 3 hours; sixthly, treating the fiber obtained in the fifth step in a 100-watt argon plasma for 10-15 minutes to obtain the oxidized boron nitride fiber described in the present application.
[0012] Preferably, the method for loading oxidized boron nitride fibers into a cancer prognosis test strip comprises the following steps: The first step is to dissolve the specific antibody, antigen or nucleic acid probe to be loaded in PBS buffer at a concentration of 1-10 micrograms per milliliter; the second step is to soak the boron nitride oxide fiber described in the present invention in the solution prepared in the first step, shake it slightly, adsorb it at 4 degrees Celsius for 1-2 hours, and wash it three times with PBS buffer after the adsorption is completed; the third step is to place the boron nitride oxide fiber obtained in the second step in a glutaraldehyde solution and soak it at room temperature for 30-60 minutes. After the soaking is completed, wash it three times with PBS buffer; the fourth step is to dry it for use.
[0013] Compared with the prior art, the present invention has the following beneficial effects: It fills the technical gap in the existing technology that there is no boron nitride cellulose nitrocellulose membrane substitute, and improves the detection sensitivity, mechanical strength and stability of cancer prognosis test strips. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is an electron microscope photograph of the boron nitride oxide fiber of Example 1 of the present invention magnified 80 times (scale: 1 mm).
[0015] Figure 2 This is an electron microscope photograph of the boron nitride oxide fiber of Example 1 of the present invention magnified 2000 times (scale: 50 microns).
[0016] Figure 3 This is an electron microscope photograph of the boron nitride oxide fiber of Example 1 of the present invention, magnified 500,000 times (scale: 1 micron). DETAILED DESCRIPTION
[0017] The above contents of the present invention are further described in detail below by means of specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. Among them, the instruments and reagents used in the examples can all be commercially available.
[0018] Example 1 Preparation of Boron Nitride Oxide Fiber The first step is to dissolve 15 grams of TEA-B and triethoxyborane in a molar ratio of 1:1.7 in 100 mL of anhydrous ethanol, and add 0.1 ml of hydrochloric acid; the second step is to stir the solution formed in the first step at room temperature for 2 hours until a uniform sol is formed; the third step is to extrude the sol prepared in the second step through a wet spinning process using a spinneret with a diameter of 0.2 mm, the ambient temperature is 25 degrees Celsius, and the humidity is 40%; the fourth step is to dry the initial fiber obtained in the third step at 80 degrees Celsius for 8 hours; the fifth step is to preheat and decompose the gel fiber obtained in the fourth step at 500 degrees Celsius in nitrogen for 1 hour, then raise the temperature to 1200 degrees Celsius, and heat treat for 3 hours in a nitrogen atmosphere with an oxygen content of 0.1%; the sixth step is to treat the fiber obtained in the fifth step in 100 watts of argon plasma for 15 minutes to obtain the oxidized boron nitride fiber described in the present application, as shown in the attached Figure 1 , Attachment Figure 2 , Attachment Figure 3 As shown. Among them, the diffraction angle of the XRD characteristic peak of the oxidized boron nitride fiber is consistent with the characteristic peak of the oxidized boron nitride standard (JCPDS-29-1216). In addition, the oxygen content of the oxidized boron nitride fiber is 38.7%.
[0019] Example 2-6 Preparation of Boron Nitride Oxide Fiber Examples 2-6 are respectively preparations of a type of oxidized boron nitride fiber, and their steps are basically the same as those of Example 1, except that the only difference is the amount of raw materials used and the process parameters, as shown in Table 1 below: ; At the same time, the diffraction angles of all XRD characteristic peaks of oxidized boron nitride fibers are consistent with the characteristic peaks of oxidized boron nitride standards (JCPDS-29-1216).
[0020] Example 7 Loading of Boron Nitride Oxide Fibers in Cancer Prognosis Test Strips The first step is to prepare 0.02M phosphate buffer (pH7.4), Tris buffer (pH 9.0), and effector solution (4wt% glycerol, 0.3wt% Kathon CG, 0.05wt% soy lecithin, 0.04wt% bovine serum albumin, and 0.02wt% lactose) respectively; the second step is to prepare the streaking solution for the test strip T line (anti-FAM antibody diluted to 2mg / mL with the phosphate buffer prepared in the first step) and the streaking solution for the test strip C line (biotinylated bovine serum albumin diluted to 20μg / mL with the phosphate buffer prepared in the first step); the third step is to soak the conjugate pad in 100mL of the mixed solution prepared by mixing the buffer prepared in the first step with the effector in a volume ratio of 1:1 for 1 minute and then dry it at 68 degrees Celsius, then spray the fluorescent microspheres labeled with streptavidin and the anti-FAM antibody on the conjugate pad at a volume of 6μL / cm and dry it; The fourth step is to soak the sample pad in 100mL of a mixed solution prepared by mixing the buffer solution prepared in the first step with the effector in a volume ratio of 1:1 for 1 minute and then dry it at 68 degrees Celsius; the fifth step is to dissolve the TNFRSF13B antibody and the CA125 antibody in PBS buffer respectively, with a concentration of 2 micrograms per milliliter; the sixth step is to soak the oxidized boron nitride fiber prepared in Example 1-6 in the solution prepared in the first step, shake it slightly, adsorb it at 4 degrees Celsius for 1.5 hours, and wash it with PBS buffer three times after the adsorption is completed; the seventh step is to place the oxidized boron nitride fiber obtained in the sixth step in a glutaraldehyde solution and soak it at room temperature for 32 minutes. After the soaking is completed, wash it with PBS buffer three times and dry it; the eighth step is to use the marking liquid prepared in the second step to mark the oxidized boron nitride fiber, and the marking amount is 0.5μL / cm. After the marking is completed, dry it; the sixth step is to stick the nitrocellulose membrane on the sticky PET The middle part of the backing; the seventh step, connecting the two ends of the boron nitride oxide fiber to the absorbent pad and the binding pad respectively, the overlapping width of the nitrocellulose membrane and the absorbent paper is 1.5mm, and the overlapping width of the boron nitride oxide fiber and the binding pad is 2.5mm; the eighth step, covering the sample pad on the binding pad, fixing the PET backing, and then cutting; the ninth step, adding a card shell to the paper strip cut in the eighth step, aligning the sample loading window with the sample pad, and aligning the signal reading window with the detection line and the quality control line respectively.
[0021] Example 8 Performance test of oxidized boron nitride fiber in cancer prognosis test strip (I) The boron nitride oxide fibers of Examples 1-6 were loaded into cancer prognosis test strips and subjected to a detection sensitivity test. The main contents are as follows: The first step is to take the boron nitride oxide fiber cancer prognosis test strips prepared in Examples 1-6 and the nitrocellulose membrane cancer prognosis test strips in the prior art (referred to as "existing" in Table 2) and use them in the process of ovarian cancer prognosis monitoring based on TNFRSF13B and CA125; In the second step, the test kit interpretation results of each cancer prognosis test strip are shown in Table 2 below: ; From Table 2, we can see that the linear correlation coefficients R 2 All are greater than 0.99. This indicates that the test results are reliable. In addition, the detection sensitivity and maximum detection range of each test strip in Examples 1-6 are better than the nitrocellulose membrane cancer prognosis test strip in the prior art. This shows that the boron nitride fiber cancer prognosis test strip provided by the present invention has a higher detection sensitivity and a larger detection range than the nitrocellulose cancer prognosis test strip in the prior art.
[0022] Example 9 Performance test of oxidized boron nitride fiber in cancer prognosis test strip (II) The mechanical strength test of the boron nitride oxide fibers of Examples 1-6 was carried out after loading in the cancer prognosis test strips. The main contents are as follows: The first step is to take the boron nitride oxide fiber cancer prognosis test strips prepared in Examples 1-6 and the nitrocellulose membrane cancer prognosis test strips in the prior art (referred to as "existing" in Table 3) and perform mechanical strength tests respectively; In the second step, the mechanical strength test results of each cancer prognosis test strip are shown in Table 3 below: ; As can be seen from Table 3, the mechanical strength test results of each test strip of Examples 1-6 are better than the nitrocellulose membrane cancer prognosis test strip in the prior art. This shows that the boron nitride oxide fiber cancer prognosis test strip provided by the present invention has better mechanical strength than the nitrocellulose membrane cancer prognosis test strip in the prior art.
[0023] Example 10 Performance test of oxidized boron nitride fiber in cancer prognosis test strip (III) The storage stability test of the boron nitride oxide fibers of Examples 1-6 was carried out after being loaded into the cancer prognosis test strips. The main contents are as follows: The first step is to take the boron nitride oxide fiber cancer prognosis test strips prepared in Examples 1-6 and the nitrocellulose membrane cancer prognosis test strips in the prior art (referred to as "existing" in Table 4) and conduct storage stability tests; In the second step, the storage stability test results of each cancer prognosis test strip are shown in Table 4 below: ; As can be seen from Table 4, the storage stability test results of each test strip of Examples 1-6 are better than the nitrocellulose membrane cancer prognosis test strip in the prior art. This shows that the boron nitride oxide fiber cancer prognosis test strip provided by the present invention has better storage stability than the nitrocellulose membrane cancer prognosis test strip in the prior art.
[0024] In summary, it can be seen that the boron nitride oxide fiber provided by the present invention has a high clinical application value for the test strip detection of ovarian cancer prognosis based on TNFRSF13B and CA125.
[0025] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. The use of boron nitride oxide fiber is characterized by: The use is to use the oxidized boron nitride fiber as a substitute for nitrocellulose membrane in a cancer prognosis test strip, the cancer is ovarian cancer, and the preparation method of the oxidized boron nitride fiber comprises the following steps: the first step is to dissolve 10-20 grams of TEA-B and triethoxyborane in a molar ratio of 1:1.5-2 in 100 mL of anhydrous ethanol, and adding 0.1 ml of hydrochloric acid; the second step, stirring the solution formed in the first step at room temperature for about 2 hours until a uniform sol is formed; the third step, extruding the sol prepared in the second step through a wet spinning process using a spinneret with a diameter of 0.2-0.5 mm, the ambient temperature is 20-25 degrees Celsius, and the humidity is 40-50%; the fourth step, drying the initial fiber obtained in the third step at 60-80 degrees Celsius for 12 hours; the fifth step, preheating and decomposing the gel fiber obtained in the fourth step at 500 degrees Celsius in nitrogen for 1 hour, then raising the temperature to 1200 degrees Celsius, and heat treating it in a nitrogen atmosphere with an oxygen content controlled to be 0.1-0.5% for 3 hours; the sixth step, treating the fiber obtained in the fifth step in 100 watt argon plasma for 10-15 minutes.
2. The use of the boron nitride oxide fiber according to claim 1, characterized in that: The diameter of the oxidized boron nitride fiber is 0.1-1.2 microns.
3. The use of the boron nitride oxide fiber according to claim 1, characterized in that: The mass percentage content of oxygen in the oxidized boron nitride fiber is 38.7%-40.3%.
4. The use of the boron nitride oxide fiber according to claim 1, characterized in that: The diffraction angle of the XRD characteristic peak of the oxidized boron nitride fiber is consistent with the diffraction angle of the characteristic peak of the oxidized boron nitride standard JCPDS-29-1216.
5. The use of the boron nitride oxide fiber according to claim 1, characterized in that: The oxidized boron nitride fiber has an overall electronegativity, an isoelectric point of 3-5, a zeta potential between -10 mV and -30 mV, and a surface charge density of -0.1 to -0.3 μC / cm².
6. The use of the boron nitride oxide fiber according to claim 1, characterized in that: The method for loading the oxidized boron nitride fiber in the cancer prognosis test strip comprises the following steps: the first step is to dissolve the specific antibody, antigen or nucleic acid probe to be loaded in PBS buffer at a concentration of 1-10 micrograms per milliliter; the second step is to immerse the oxidized boron nitride fiber in the solution prepared in the first step, shake it slightly, adsorb it at 4 degrees Celsius for 1-2 hours, and wash it with PBS buffer for 3 times after the adsorption is completed; the third step is to place the oxidized boron nitride fiber obtained in the second step in a glutaraldehyde solution and soak it at room temperature for 30-60 minutes, and wash it with PBS buffer for 3 times after the soaking is completed; the fourth step is to dry it for use.